The silvered - Huff, Tanya (DAW book collectors, 2012)
The Empire has declared war on the small, were-ruled kingdom of Aydori, capturing five women of the Mage-pack, including the wife of the were pack-leader. With the pack off defending the border, it falls to Mirian Maylin and Tomas Hagen, she a low-level mage, he younger brother to the pack-leader, to save them.